O Plano Nacional de Educação 2014–2024 e os desafios para a Educação Especial na perspectiva de uma Cultura Inclusiva - Macena, Janaina De Oliveira; Justino, Laura Regina Paniagua; Capellini, Vera Lúcia Messias Fialho (Fundação CESGRANRIO, 2018)
Abstract This study deals with Brazil’s efforts to implement educational public policies aimed at creating an Inclusive Culture. A brief historical review related to the struggles that have been made until today (when public policies connected to this subject finally exist) to guarantee rights is presented. The analysis is done with the collection of indicators for goal 4 of the National Education Plan that deals with the formation of actions focused on Inclusive Education for the next decade. In this sense, data are presented on the evolution of enrollment of students with disabilities; on the training of teachers that are able to attend this specific audience; and on the implementation and usage of multifunctional resource rooms. The references come from the database of INEP (National Institute of Studies and Educational Research Anísio Teixeira). Analyzed data consider the crossing between the numbers of the School Census and the Demographic Census of IBGE (Brazilian Institute of Geography and Statistics).

Resumen Este estudio se sitúa ante los caminos que vienen siendo trillados en Brasil en la implementación de políticas públicas en el área de la educación, orientadas hacia una Cultura Inclusiva. Se presenta un breve relevamiento histórico sobre el trayecto de las luchas sociales, en la garantía de derechos, hasta el momento en que políticas públicas están atentas a ese tema. El recorte analítico se da en el levantamiento de indicadores para la meta 4 del Plan Nacional de Educación, la cual establece la planificación de acciones dirigidas a la Educación Inclusiva para la próxima década. En este sentido, se presentan datos sobre: la evolución de las matrículas de alumnos con discapacidad, formación de docentes para atender a esos públicos específicos y relativos a la implantación y al uso de las salas de recursos multifuncionales. Las referencias utilizadas proceden de la base de datos del INEP (Instituto Nacional de Estudios e Investigaciones Educativas Anísio Teixeira). Los datos analizados consideran el cruce de los números del Censo Escolar y del Censo Demográfico del IBGE (Instituto Brasileño de Geografía y Estadística).

Resumo Este estudo situa-se diante dos caminhos que vêm sendo trilhados no Brasil na implementação de políticas públicas na área da educação, voltadas para uma Cultura Inclusiva. Apresenta-se um breve levantamento histórico sobre o trajeto das lutas sociais, na garantia de direitos, até o presente momento em que políticas públicas estão atentas a esse tema. O recorte analítico se dá no levantamento de indicadores para a meta 4 do Plano Nacional de Educação, a qual estabelece o planejamento de ações voltadas à Educação Inclusiva para a próxima década. Nesse sentido, são apresentados dados sobre: a evolução das matrículas de alunos com deficiência, formação de docentes para atender a esse público específico e relativos à implantação e ao uso das salas de recursos multifuncionais. As referências utilizadas são provenientes da base de dados do INEP (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira). Os dados analisados consideram o cruzamento dos números do Censo Escolar e do Censo Demográfico do IBGE (Instituto Brasileiro de Geografia e Estatística).
The National Education Plan 2014–2024 and the challenges for Special Education in the perspective of an Inclusive Culture
El Plan Nacional de Educación 2014–2024 y los desafíos para la Educación Especial en la perspectiva de una Cultura Inclusiva
Keywords: National Education Plan 2014–2024; Inclusive Education; Inclusive Culture; Plano Nacional de Educação 2014–2024; Educação Inclusiva; Cultura Inclusiva